Efeitos cardiovasculares e respiratórios da morfina, metadona, nalbufina ou butorfanol em cães conscientes - Alvares, Ellen Mireille (2011)
Opioids are effective in pain treatment being extensively used in veterinary medicine. However, these agents tend to cause physiological alterations that need to be study. Therefore, this study aimed to evaluate the cardiovascular and respiratory changes caused by the use of different opioids intramuscularly in conscious dogs. For that, six animals were used in four treatments: morphine (TMO), methadone (TME), nalbuphine (TNA) and butorphanol (TBU). We evaluated the electrocardiogram [P wave duration and amplitude (Pms and PmV), PR interval (PR), QRS (QRS) and QT (QT) and R-wave amplitude (RmV)], heart rate (HR), sistolic arterial pressure (SAP), end tidal carbon dioxide (ETCO2), oxyhemoglobin saturation (SpO2), respiratory rate (RR), rectal temperature (RT) and sedation (S) at baseline (T0) and during 50 minutes of evaluation (T5, T10, T15, T20, T30, T40 and T50). Differences were considered significant at p  0.05. The HR was higher in the treatment with morphine and nalbuphine when compared to butorphanol in T30. In T40 and T50, HR was lower with morphine and methadone when compared to nalbuphine and butorphanol. The P-wave amplitude was lower in morphine in comparison with butorphanol at T40. Regarding RmV, baseline was lower when compared to T10 and T40 with methadone. In nalbuphine treatment, T50 was greater than the baseline. In QT interval, T20, T30 and T50 were higher than the baseline with methadone. Also in QT, animals treated with butorphanol had lower values than those treated with morphine and methadone in T40. Animals treated with methadone had RR higher than the other groups at T40. There was gradual reduction in rectal temperature in all groups. Sedation increased from T5 when compared to baseline with morphine and nalbuphine treatment. The same occurred in the treatment with butorphanol from T10 to T40. Furthermore, sedation had higher values with morphine in comparison to the other groups in T50. With the results presented in this study it was concluded that morphine, methadone, nalbuphine or butorphanol administration intramuscularly in conscious dogs do not cause significant cardiovascular changes, since administered in healthy animals, especially without cardiac abnormalities. For clinical purposes, all of them do not promote respiratory depression and do not cause significant behavioral changes. Regarding sedation, morphine is the opioid with the highest sedation when compared to other drugs studied.